(3GdZQjH GdeUfas - (3GdbGSe Hf SdGe GdgQhj GdCROj GdNRGYj, CHh YHjO, J (B224 (3g` s
(3ChdgG (B:s
(3HGH UaI Ndb GdEfSGf hfYhJg (B: (3MOKfG CHh Ydi ESeGYjd Hf GdbGSe GdHZOGOi bGd (B: (3bQC gPG GdcJGH CHj HcQ eMeO Hf GdbGSe Hf HTGQ GdCfHGQi bGd CHh YHjO GdbGSe Hf SdGe (B: (3SeYJ CHG YeQh GdTjHGfi jbhd GdCfha jbGd dgG GdeNGWe s
(3BNQgG (B:s
(3MaJ GdeQCI hLggG JMaI MakG hMaGakG Je GdLRA GdYGTQ ef GdZQjH GdeUfa , hHJeGeg Je LejY GdOjhGf s
(3GdfSNI HgG MhGTs
(3YTQI CLRGA ai eLdOs
(3YdjgG JbjjOGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs